Argentina and China: an analysis of the actors in the soybean trade and the migratory flow - Oviedo, Eduardo Daniel (2015)
This article explains who the actors are and how they interact in the two main issues concerning Argentinian–Chinese relations: the soybean trade and Chinese migration to Argentina. Each of the trade policies of the two states guides the soybean business and the Argentinian migration policy seeks to control the flow of Chinese immigration. However, the growing influence of the Chinese state on Argentina through Chinese state-owned companies and Chinese migrants has infiltrated the role played by the Argentinian state in Argentinian–Chinese relations. But the dominant role played by the Argentinian government in the alliance between the Argentinian government and the big export companies in the soybean trade, and the capacity of Argentina state to control the Chinese immigration flow in the face of non-state actors, both legal and clandestine, show that the government is still able to exert a significant restraining influence on these Chinese non-state actors.